THE PANDEMIC PARADIGM: DECODING INTELLECTUAL CAPITAL'S INFLUENCE ON INDONESIA, THAILAND, AND PHILIPPINES’ PROFITABILITY - Elsinta, Laurentia Yuke; Marlina, Maria Asumpta Evi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The COVID-19 pandemic has triggered a global decline in corporate profitability. However, it has also accelerated digital transformation, driven by intellectual capital (IC). This study examines the relationship between IC and its components (HCE, SCE, CEE, RCE, and MVAIC) and corporate profitability during the global crisis (2020-2022). Employing a quantitative approach with purposive sampling and multiple linear regression analysis, the study investigates 78 companies in Indonesia, Thailand, and the Philippines. Resource-Based Theory (RBT) elucidates IC's role as a competitive advantage. The findings reveal that CEE and SCE significantly positively impact corporate profitability, while HCE, RCE, and MVAIC exhibit no significant influence.